Capital/labor substitution, capital deepening, and FDI - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2007)
Empirical studies show that the elasticity of substitution between capital and labor is larger than one in developed countries but smaller in developing countries. This paper develops a production function which allows for this structure in the elasticity of substitution. The case of a falling real interest rate and capital deepening in the developed countries in the presence of FDI flows from the developed to the developing country is analyzed. It is shown that this structure in the elasticity of substitution can be responsible for a U-shaped relationship between the capital intensity of the developed country and the relative capital intensity of the developing country. This carries over to an inverted U-shaped relationship between the capital intensity of the developed country and FDI profitability.
urn:nbn:de:bvb:384-opus4-711394
Keywords: E23; F21; O11; 330; Capital/Labor Substitution : FDI; Capital Deepening; Faktorsubstitution; Kapitalintensität; Substitutionselastizität; Direktinvestition; Theorie; Industriestaaten; Entwicklungsländer